IL-10 Producing B Cells Ability to Induce Regulatory T Cells Is Maintained in Rheumatoid Arthritis - Mielle, Julie; Audo, Rachel; Hahne, Michael; Macia, Laurence; Combe, Bernard; Morel, Jacques; Daien, Claire (Frontiers in Immunology, 2018)
Despite growing evidence highlighting the relevance of increasing IL-10 producing B cells (B10+cells) in autoimmune diseases, their functions in patients are still unknown. The aim of the present study was to evaluate the functions of CpG induced B10+ cells isolated from healthy controls (HC) and rheumatoid arthritis (RA) patients, on naïve T cell differentiation. We demonstrated that CpG induced B10+ cells from HC drove naïve T cell differentiation toward regulatory T cells (Treg cells) and IL-10 producing T cells (Tr1) through IL-10 secretion and cellular contacts. B10+ cells from HC did not decrease T helper 1 (Th1) nor TNFα producing T cell (TNFα+ T cell) differentiation. We showed that in RA, B10+ cells could also induce Treg cells and Tr1 from naïve T cells. Contrary to HC, B10+ cells from RA patients increased naïve T cell conversion into Th1. Interestingly, PD-L2, a programmed death-1 (PD-1) ligand that inhibits PD-L1 and promotes Th1 differentiation, was overexpressed on RA B10+ cells compared to HC B10+ cells. Together, our findings showed that CpG induced B10+ cells may be used to increase regulatory T cells in patients with RA. However, CpG may not be the most adequate stimuli as CpG induced B10+ cells also increased inflammatory T cells in those patients.